From Leaves to Markets: Assessing Trade Competitiveness of Nepalese Tea in the WTO Era - Luitel, Gaurab; Panta, Hari Krishna; Dahal, Kishor Chandra; Bhusal, Tara Prasad; Timsina, Krishna Prasad (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2025)
Tea is one of the major exportable agricultural commodities of Nepal. This study explores the implications of Nepal’s accession to WTO in the tea trade with objectives of identifying potential opportunities and challenges. The study was conducted in Jhapa and Ilam through structured interview on 5 tea processing units in each district. Moreover, secondary data were obtained from the trade portals and database available at the public domains. The data collected were analysed by using quantitative techniques to make comparative analysis of the growth between pre and post WTO accession scenarios. The research also examined the trade measures and market access barriers that affects the export of Nepalese tea. The study found that WTO membership has opened up a plethora of opportunities as the increase in tea exports from Nepal can be attributed to its membership in the WTO, notably seen in the fiscal year 2003/04 when it joined WTO. Moreover, the competitive analysis using Nominal Protection Coefficient (NPC) and Domestic Resource Cost (DRC) illuminated the trade dynamics of CTC and Orthodox teas. While the findings revealed a cost-competitive edge in the export market for Orthodox tea (NPC=0.67), the export market presented challenges in case of CTC (NPC =1.15) due to over-dependence in India. The DRC ratio of 0.86 and 0.80 for CTC and orthodox tea respectively provides strong evidence that Nepal has comparative advantage in producing both types of tea.